Caracterização molecular e antigênica de Clostridium chauvoei isolados de casos de carbúnculo sintomático em bovinos - Ziech, Rosangela Estel (2018)
Clostridioses are the group of infections and intoxications caused by anaerobic microorganisms of the genus Clostridium. Among these diseases, the main disease that causes myonecrosis is blackleg, an endogenous and acute infection that mainly affects cattle, whose etiological agent is Clostridium chauvoei. Control of this disease is based on adequate management measures and systematic vaccinations of herd. Vaccines against blackleg marketed in Brazil are, in general, composed of multiple antigens and follow the standards for quality and efficiency control defined in the legislation published by the Ministry of Agriculture, Livestock and Food Supply (MAPA). However, there are few studies with scientific evidence to prove the effectiveness of the vaccine, as well as studies indicating the degree of similarity between strains of C. chauvoei used in the production of these vaccines, strains occurring in the field and the standard strain. Likewise reports of vaccine failures are informal and the circumstances of these failures are not clearly elucidated. The main virulence factors of C. chauvoei are neuraminidase, cytotoxin A (CctA) and flagellin, and CctA appears to be the main. This thesis aimed to evaluate the protective efficacy of commercial vaccines against the challenge with C. chauvoei, as well as to carry out the genomic comparison of the strains used in the vaccine challenge (manuscript 2). The molecular diversity, from the partial sequencing of the neuraminidase (nanA), CctA (cctA) and flagellin (fliC) genes of seventeen strains of C. chauvoei isolated from clinical cases in cattle was investigated (manuscript 3). It also aimed to the genomic comparison of six strains isolated from cases of blackleg in Brazil with a view to investigate molecular differences in the only strain with visceral clinical presentation (manuscript 4). Thus, to discuss the implications of molecular and antigenic characterization in the understanding of blackleg, and to support future research with the objective of improving disease control. We concluded that the similar performance observed between the strains in challenge in vivo and the inability to infect the vaccinated animals are correlated with the genetic homology of the strains, suggesting that vaccine failures are not related to antigenic variability. Partial sequencing of nanA and cctA genes showed high homology between strains. For this reason, these soluble antigens are good candidates for vaccine antigens. Moreover, three different fliC alleles were detected among the strains studied. In the genomic comparison, the six Brazilian strains were highly conserved, as observed in the partial sequencing of the genes and in the comparison of the strains used in the vaccine challenge. The results presented in this thesis may be indicative that at this evolutionary time C. chauvoei is not being challenged to develop mutations.